Portrait of Physical Education Teachers' Readiness for Students with Special Needs: A Case Study in Inclusive Schools - Ulin Nafi' Fibriani; Abdul Rachman Syam Tuasikal; Anung Priambodo; Nur Winawan Yunistira Winarno (STKIP Pasundan Press, 2026)
Inclusive physical, sports, and health education (PJOK) learning requires teachers' readiness to assist students with special needs (MBK). This study aims to analyze the level of readiness of PJOK teachers in inclusive schools from the dimensions of knowledge, skills, attitudes, and readiness for collaboration and their differences based on inclusive teaching and training experience. The study used a quantitative approach with a descriptive-comparative survey design of PJOK teachers in inclusive schools in Tambaksari District, Surabaya, which was selected through purposive techniques and total sampling. Data were collected using a five-level Likert scale questionnaire that had met validity and reliability tests, then analyzed using descriptive statistics, independent t-tests, and one-way ANOVA. The results showed that the readiness of PJOK teachers was in the good to very good category with an average knowledge of 3.23–4.33, skills 3.73–4.30, attitude 3.83–4.57, and collaboration 3.80–4.40; teachers who participated in inclusive training had a higher readiness score (M = 199.48) than teachers who did not participate in the training (M = 172.00), while teaching experience showed no significant difference (F = 0.694; p = 0.508). It was concluded that inclusive training plays an important role in increasing the readiness of PJOK teachers to carry out inclusive learning effectively.